Hydration studies of calcium sulfoaluminate cements blended with fly ash - García-Maté, Marta; Gómez-de-la-Torre, María de los Ángeles; León-Reina, Laura; García-Aranda, Miguel Ángel; Santacruz-Cruz, María Isabel (Elsevier, 2013)
The main objective of this work is to study the hydration and properties of calciumsulfoaluminate cement pastes blended with fly ash (FA) and the corresponding mortars at different hydration ages. Laboratory X-ray powder diffraction, rheological studies, thermal analysis, porosimetry and compressive strength measurements were performed. The analysis of the diffraction data by Rietveld method allowed quantifying crystalline phases and overall amorphous contents. The studied parameters were: i) FA content, 0, 15 and 30 wt.%; and ii) water addition, water-to-CSA mass ratio (w/CSA = 0.50 and 0.65), and water-to-binder mass ratio (w/b = 0.50). Finally, compressive strengths after 6 months of 0 and 15 wt.% FA [w/CSA = 0.50] mortars were similar: 73 ± 2 and 72 ± 3 MPa, respectively. This is justified by the filler effect of the FA as no strong evidences of reactivity of FA with CSA were observed. These results support the partial substitution of CSA cements with FA with the economic and environmental benefits
Keywords: Cemento; X-Ray diffraction analysis; Hydration; Compressive strength; Sulfoaluminate; Blended cement